2020
DOI: 10.12998/wjcc.v8.i16.3591
|View full text |Cite
|
Sign up to set email alerts
|

Giant benign phyllodes breast tumour with pulmonary nodule mimicking malignancy: A case report

Abstract: BACKGROUND Phyllodes tumours (PTs) are fibroepithelial breast tumours, which can be classified as benign, borderline or malignant, according to their histological characteristics. While various huge borderline or malignant PTs have been previously described, a benign PT with a pulmonary nodule mimicking malignancy has not yet been reported. In order that doctors may have a comprehensive understanding of super-giant benign PTs (≥ 20 cm), we also performed a literature review to summarize the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…When a PT has a diameter above 10 cm, it can be classified as a giant PT [ 12 ]. Most of the cases in our review presented local signs of inflammation, venous congestion [ 13 , 14 ], bleeding [ 10 , 15 , 16 ], “peau d’orange” [ 17 , 18 ] or even necrosis or skin ulcers [ 7 , 10 , 14 , 15 , 16 , 19 , 20 , 21 ] while others had no other clinical manifestation than the enlargement of the affected breast [ 22 , 23 , 24 , 25 ]. Local complications are attributed to the increased pressure that the rapid tumoral growth exerts on the skin but can be difficult to interpret since they are encountered also in malignancy [ 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a PT has a diameter above 10 cm, it can be classified as a giant PT [ 12 ]. Most of the cases in our review presented local signs of inflammation, venous congestion [ 13 , 14 ], bleeding [ 10 , 15 , 16 ], “peau d’orange” [ 17 , 18 ] or even necrosis or skin ulcers [ 7 , 10 , 14 , 15 , 16 , 19 , 20 , 21 ] while others had no other clinical manifestation than the enlargement of the affected breast [ 22 , 23 , 24 , 25 ]. Local complications are attributed to the increased pressure that the rapid tumoral growth exerts on the skin but can be difficult to interpret since they are encountered also in malignancy [ 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…CT of the cervix, thorax, abdomen, and pelvis confirmed cervical and axillary lymphadenopathy and was useful in excluding distant metastases or other tumoral pathology, but not for characterization of primary lesions since it lacks specificity for breast tissue. The presence of a pulmonary nodule can mimic a metastasis as Zhang et al reported [ 15 ]. In our case, the nodule was small, without tumoral features, but determined us to perform a follow-up CT at six months.…”
Section: ⧉ Discussionmentioning
confidence: 99%